Front-Find Design for Ka Band mm-Wave Radar - Keskin, Ahmet Kenan; Senturk, Mustafa Dagcan; Demirel, Salih; Kizilay, Ahmet; Turk, Ahmet Serdar (IEEE, 2016)
In this paper front-end design for a Ka band milimeter wave (MMW) radar which consists of an antenna, a low noise amplifier (LNA) and a band pass filter is presented. The operation frequency of the designed system is between 24-25 GHz in Ka band. A high gain axially displaced elliptical (ADE) dual reflector antenna is employed on the antenna structure. ADE sub-reflector with 5 cm diameter is illuminated by a feeder horn and a main reflector 30 cm diameter parabola focuses incoming waves from the ADE sub-reflector. According to the simulation results narrow half power beam width (HPBW=30(0)) and high gain (G=35 dBi) are obtained with good efficiency (%58). An HJ-FET that has low noise figure (NF 13 dB) is utilized to design a LNA. Double transistors are connected as cascaded to achieve higher transducer gain (GT>19 dB). Matching circuits and feeder resonators are designed by microstrip lines to obtain low input and output VSWR (V-in -2.5dB) and low return loss (S-11<-15 dB) are aimed to take signal as lossless as at pass band. The simulated designs are manufactured and measured. It is seen that there are good agreements between measurement and simulation results.
Keywords: Front-End; mm-Wave; Low Noise Amplifier; Reflector Antenna; Band Pass Filter; Engineering; Telecommunications